COMPUTATIONAL FLUID DYNAMICS SIMULATION OF KARTINI REACTOR FUELED PLATE - Tri Nugroho Hadi Susanto (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2019)
The purpose of this study is to determine the characteristics of the cooling system on the new design of the Kartini Reactor plate fuel based on numerical calculations (Computational Fluid Dynamics). The fuel plate model was simplified and made in 3D. The model dimensions are 17.3 mm x 68 mm x 900 mm. The space between the two plates called the narrow rectangular channels has a gap of 2 mm. On these simulations a heat flux of 10612,7 watt/m2 was used which was obtained from the MCNP calculation program. Simulations were conducted in a steady state condition and single-phase model laminar flow of an incompressible fluid through the gap between the two fuel plates. This simulation uses UDF (User Define Function) to approach heat flux behaviour that follows the neutron distribution in the reactor core. The simulation results show that the maximum temperature that occur at a flow rate of 0.01 m/s was 43.5 °C.